What is 9/3 plus 6/3?
Looking for the result of 9/3 + 6/3? Follow this step-by-step guide to understand how to add these two fractions together.
How to add 9/3 and 6/3?
- Multiply the numerator of the first term, with the denominator of the second term: 9 × 3 = 27
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 3 = 18
- Add both of these results together to form the new numerator: 27 + 18 = 45
- Multiply both denominators together to form the new denominator: 3 × 3 = 9
- Combine the results to get the new fraction: 45/9
- Simplify the fraction (45/9) by dividing both the numerator and the denominator by their GCD (9):
- 45/9 = 5
- 9/9 = 1
- This gives: 5.
The result of adding 9/3 and 6/3 is : 5